Relevansi Ajaran Tasawuf Bagi Kehidupan Muslim di Era Modern - Puthut Waskito (Islamic University of Indonesia, 2021)
This research is based on the fact that materialistic culture is in rise andspread across Muslim society. Almost all aspects of life are judged only bymaterial measures. On that basis, the author sees the relevance of Sufiteachings. This research is conduct through library research methode. Theprimary data sources in this study are Sufi literature and the socialcondition of Muslim community. The secondary data sources were obtainedfrom several writings from Sufis observer and the results of Sufipractitioners in alleviating various problems and providing varioussolutions to the society. The results of this study indicate that the morals ofSufism as exemplified by the Prophet Muhammad are very relevant ifapplied to the current modern era. In addition, various ahwal conditions orspiritual conditions such as qurbah, khauf and raja' can contribute to peaceof mind and human peace in everyday life in today's modern era. Especiallyit can reduce the condition of the soul which always refers to the aspect ofmaterialism which is only focused on outward needs.Keywords: Sufism teaching; Noble character; Materialism; Modern Era.